KEPEMILIKAN MANAJERIAL DALAM MENDUKUNG KECEPATAN WAKTU PENYAMPAIAN INTERNET FINANCIAL REPORTING - Dina Alafi Hidayatin` (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2020)
This study aims to prove whether the mechanism of good corporate governance can affect the speed of delivery of internet financial reporting. The study was conducted on 137 manufacturing companies that went public on the Indonesia Stock Exchange in 2012 - 2014. The number of samples was determined using a purposive sampling method by applying several criteria. Data analysis techniques in this study used logistic regression. The results that can be concluded after conducting a data analysis are that the mechanism of good corporate governance does not affect the speed of delivery of internet financial reporting, either partially or simultaneously.